Prerequisites for the integration of Central Asian countries (International relations and international law Journal, 2018)
This article discusses the prerequisites for the integration of Central Asian countries. At the same time, in the opinion of the authors, for greater convergence of the countries of Central Asia, each of them has its own pros and cons. It describes the pros and cons of closer integration for each of the countries in the region, emphasizing that certain prerequisites for this are available. Plus, the article analyzes the integration of Central Asian countries from a historical point of view, describing the prob- lems that arose on this path in the 1990s. still devoted to describing the similarities and differences     of the post-soviet countries of Central Asia, which can both facilitate and hinder normal cooperation.  In the conclusion it is claimed that «Kazakhstan can become a» locomotive «of regional economic development and therefore intends to act as a pole of integration of the Central Asian countries and   to take an active part in the formation of a dynamic market throughout the region». The article also examines the factors that contribute to the real integration of Central Asian countries. Authors give historical facts confirming the prospects of this process for each country in the region, and also coor- dinate this process with the membership of states in various international and regional organizations. Under the assumptions, we mean those objective conditions and trends that can facilitate or hinder  the implementation of a project. This article discusses the prerequisites for the economic integration  of the Central Asian countries as a set of objective conditions that imply closer cooperation between the countries of the region in order to solve common problems and ensure the economic development of each of them, as well as the trends in the world economy that have been manifested in recent years and are characterized by increased protectionist moods in the leading economic powers of the world that can exert their influence in the integration processes in the decisions of Central Asia. Factors      that could have a negative impact on the integration processes in the region include processes that began in the 1990s with the collapse of the USSR and manifested themselves in various approaches     to economic reform and the pace of their implementation, in selected forms of political organization   of countries, in national priorities in various spheres of social life, etc. Much will depend on the posi- tions of international organizations interested in the problems of the region and integration groups     in which the members are the countries of Central Asia. In conclusion, we believe that the positive prerequisites for economic integration outweigh the negative and the future of the countries of the region objectively linked to integration among themselves and Kazakhstan can be the «locomotive» of economic integration in the region.Key words: integration, positive and negative prerequisites, objective prerequisites, preconditions,preventing integration, Central Asia, countries of the region.